Dutch courage? Effects of acute alcohol consumption on self-ratings and observer ratings of foreign language skills. (January 2018) - Renner, Fritz; Kersbergen, Inge; Field, Matt; Werthmann, Jessica
Aims: A popular belief is that alcohol improves the ability to speak in a foreign language. The effect of acute alcohol consumption on perceived foreign language performance and actual foreign language performance in foreign language learners has not been investigated. The aim of the current study was to test the effects of acute alcohol consumption on self-rated and observer-rated verbal foreign language performance in participants who have recently learned this language. Methods: Fifty native German speakers who had recently learned Dutch were randomized to receive either a low dose of alcohol or a control beverage that contained no alcohol. Following the experimental manipulation, participants took part in a standardized discussion in Dutch with a blinded experimenter. The discussion was audio-recorded and foreign language skills were subsequently rated by two native Dutch speakers who were blind to the experimental condition (observer-rating). Participants also rated their own individual Dutch language skills during the discussion (self-rating). Results: Participants who consumed alcohol had significantly better observer-ratings for their Dutch language, specifically better pronunciation, compared with those who did not consume alcohol. However, alcohol had no effect on self-ratings of Dutch language skills. Conclusions: Acute alcohol consumption may have beneficial effects on the pronunciation of a foreign language in people who have recently learned that language.